MODY type 2 P59S GCK mutant: founder effect in South of Italy. (26th March 2012) - Delvecchio, M; Ludovico, O; Bellacchio, E; Stallone, R; Palladino, T; Mastroianno, S; Zelante, L; Sacco, M; Trischitta, V; Carella, M
<x xml:space="preserve">Abstract</x> Delvecchio M, Ludovico O, Bellacchio E, Stallone R, Palladino T, Mastroianno S, Zelante L, Sacco M, Trischitta V, Carella M. MODY type 2 P59S GCK mutant: founder effect in South of Italy. Mutations in the glucokinase (GCK) gene are the most frequent cause of maturity onset diabetes of the young (MODY) in Italy. We evaluated GCK mutations in 32 unrelated patients younger than 18 years who had been diagnosed with MODY. Eleven different GCK heterozygous mutations were identified in 22 (68.7%) of the 32 probands. Nine mutations were missense and two were nonsense. Three of these mutations (E17X, P59S and E372X) have not been described previously and were shown to be associated with hyperglycaemia. Several prediction methods suggested that the E17X and E372X mutations result in a premature truncated protein and that the P59S mutation is pathogenic. This idea was further supported by evidence suggesting that Proline 59 is a highly conserved amino acid residue and that the P59S mutation does not appear to be present in non‐diabetic controls and in sequence variant databases. Furthermore, this mutation was found in six (27.3%) of the patients from the same geographical area, Gargano, pointing to the existence of a founder effect, which was confirmed by microsatellite analysis.